Sulfite Oxidase Activity Is Essential for Normal Sulfur, Nitrogen and Carbon Metabolism in Tomato Leaves - Brychkova, Galina (Plants (Basel), 2015)
Plant sulfite oxidase [SO; E.C.1.8.3.1] has been shown to be a key player in protecting plants against exogenous toxic sulfite. Recently we showed that SO activity is essential to cope with rising dark-induced endogenous sulfite levels in tomato plants (Lycopersicon esculentum/Solanum lycopersicum Mill. cv. Rheinlands Ruhm). Here we uncover the ramifications of SO impairment on carbon, nitrogen and sulfur (S) metabolites. Current analysis of the wild-type and SO-impaired plants revealed that under controlled conditions, the imbalanced sulfite level resulting from SO impairment conferred a metabolic shift towards elevated reduced S-compounds, namely sulfide, S-amino acids (S-AA), Co-A and acetyl-CoA, followed by non-S-AA, nitrogen and carbon metabolite enhancement, including polar lipids. Exposing plants to dark-induced carbon starvation resulted in a higher degradation of S-compounds, total AA, carbohydrates, polar lipids and total RNA in the mutant plants. Significantly, a failure to balance the carbon backbones was evident in the mutants, indicated by an increase in tricarboxylic acid cycle (TCA) cycle intermediates, whereas a decrease was shown in stressed wild-type plants. These results indicate that the role of SO is not limited to a rescue reaction under elevated sulfite, but SO is a key player in maintaining optimal carbon, nitrogen and sulfur metabolism in tomato plants.